Iron Supplement Consumption, Dietary Intake, Nutritional Status, and Anemia Among Adolescent Girls in Banawa, Donggala Regency - Nasrul, Nasrul; Hafid, Fahmi; Taqwin, Taqwin; Hikmah; Risma; Nuswantari, Atika; Sariman, Sarina (Journal of Health and Nutrition Research, 2025)
This study aimed to examine the relationship between iron supplement consumption, dietary intake, nutritional status, and anemia among adolescent girls in Banawa, Donggala Regency. A cross-sectional analytical design was applied, involving 231 female students aged 12–15 years from SMP Negeri 3 and SMK Negeri 2 Banawa. Stratified sampling was used, and data were collected through interviews using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), anthropometric measurements, and hemoglobin testing via Point of Care Testing (POCT). Nutrient intake was assessed based on 80% adequacy of the Indonesian Recommended Dietary Allowance (RDA), while anemia was defined as hemoglobin levels <12 g/dL. Compliance with iron supplementation was determined using a median-based scoring method. The results revealed a high anemia prevalence (71.0%) among participants. Although 61.0% were compliant with iron supplementation, no significant association was found between supplement compliance and anemia status. Likewise, protein and iron intake showed no significant relationships. However, vitamin C intake was significantly associated with anemia (p = 0.001), indicating its crucial role in iron absorption. Nutritional status and iron inhibitor intake were not significantly related to anemia. The findings highlight the need for integrated school-based nutrition programs focusing on improving vitamin C intake and promoting effective iron supplementation practices.